To solve this problem using Hess's Law, we need to manipulate the given reactions and their enthalpy changes to match the target reaction. Target reaction: 2H2S g + 3O2 g 2H2O l + 2SO2 g 1. Reverse the third reaction and multiply by 2: 2H2S g 4H2 g + 2S s H3' = -50 kJ2. Add the first reaction to the modified third reaction: 4H2 g + 2S s + 2H2 g + O2 g 4H2O l + 2S s + 2SO2 g H = H1 + H3' = -484 kJ - 50 kJ = -534 kJ3. Now we have the reaction: 4H2 g + 2S s + O2 g 4H2O l + 2SO2 g 4. Divide the entire reaction by 2 to match the target reaction: 2H2S g + 3O2 g 2H2O l + 2SO2 g H = -534 kJ / 2 = -267 kJThe enthalpy change for the target reaction is -267 kJ.